Islamic Education Dynamic in The Epistemology of Learning Theory - Ava Swastika Fahriana (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
This article aims to explore new epistemological paradigm of Islamic education of qodrati potency-based learning. The development of various views, understandings and theories about the learning process is essentially tge development of the essence of the learning process, along with the demands of the development of society where the learning process itself takes place. It is undeniable that today globalization era will always go on with the increasing complexity of society's need for educational graduates who are expected to have complete capabilities in various fields. Historically, it has been has noted that there are many changes and developments in the world of education, both related to the management of education and learning process. Learning theories that have been used and continue to develop include behaviorism, connectionism, and classical habituation, and behavior habituation, habituation of close association, cognitive theory, and social learning theory. The ongoing changes in society require that every graduate of a school has the ability to act, learn and manage its own future independently by integrating the best elements of successful systems. Meanwhile, Islamic epistemology has a very strategic role in the effort to combine and choose the various approaches of learning so that the learning pattern leads to the development of the potential qodrati of learning participants. Thus, educational objectives can be reached through potential qodrati-based learning.